Memorials : a novel - Chizmar, Richard, 1965- (Gallery Books, 2024)
"1983: Three students from a small college embark on a week-long road trip to film a documentary on roadside memorials for their American Studies class. The project starts out as a fun adventure with long stretches of empty road and nightly campfires where they begin to open up with one another. But as they venture deeper into the Appalachian backwoods, the atmosphere begins to darken. They notice more and more of the memorials feature a strange, unsettling symbol hinting at a sinister secret. Paranoia sets in when it appears they are being followed. Their vehicle is tampered with overnight and some of the locals appear to be anything but welcoming. Before long, the students can't help but wonder if these roadside deaths were really random accidents...or is something terrifying at work here?"--